2012
DOI: 10.1007/s12015-012-9410-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Basis and New Insights for Cell Therapy in Chronic Obstructive Pulmonary Disease

Abstract: Chronic Obstructive Pulmonary Disease (COPD) can be briefly described as air flow limitation and chronic dyspnea associated to an inflammatory response of the respiratory tract to noxious particles and gases. Its main feature is the obstruction of airflow and consequent chronic dyspnea. Despite recent advances, and the development of new therapeutic, medical and clinical approaches, a curative therapy is yet to be achieved. Therapies involving the use of tissue-specific or donor derived cells present a promisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 53 publications
2
13
0
18
Order By: Relevance
“…Several studies have demonstrated the potential therapeutic effect of MSCs in different diseases: myocardial infarction [41,42,43,44], pulmonary fibrosis [45,46], pulmonary hypertension [47,48,49,50], emphysema [51,52,53], diabetes [54], sepsis [55,56], asthma [57], hepatic failure [58], acute renal failure [59] and ARDS [5,38,60,61,62,63,64]. In all preclinical studies, infused MSCs expanded in vitro were used.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Several studies have demonstrated the potential therapeutic effect of MSCs in different diseases: myocardial infarction [41,42,43,44], pulmonary fibrosis [45,46], pulmonary hypertension [47,48,49,50], emphysema [51,52,53], diabetes [54], sepsis [55,56], asthma [57], hepatic failure [58], acute renal failure [59] and ARDS [5,38,60,61,62,63,64]. In all preclinical studies, infused MSCs expanded in vitro were used.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Há vários estudos na literatura que mostram a migração celular para o pulmão, após a infusão de células em vasos periféricos (Adachi et al, 2006;Faria et al, 2012;Katsha et al, 2011;Kotton et al,2001;Krause et al, 2001;Lama et al,2007;Longhini-dos-Santos et al, 2013;Neuringer, Radell, 2004;Pereira et al,1995;Ribeiro-Paes et al, 2009, 2011, 2012Schrepfer et al, 2007;Sueblinvong, Weiss, 2010;Suratt et al,2003;Yamada et al,2004). Células infundidas na circulação periférica são levadas diretamente para o pulmão, o que torna esta estratégia de infusão passível de ser aplicada em modelos experimentais e terapia celular experimental em pacientes humanos.…”
Section: Discussionunclassified
“…Desta forma, muitos modelos animais de DPOC têm sido propostos por diferentes grupos de pesquisadores que buscam uma maior compreensão da fisiopatologia, bem como alternativas que sejam eficazes no tratamento do enfisema (Cazzola et al, 2007;Faria et al, 2012;Fusco et al, 2002;GOLD, 2009;Gross et al, 1965;Hele, 2002;Hyatt et al, 2000;Longhini-dos-Santos et al, 2013;Mahadeva, Shapiro, 2002;Martorana et al, 1989;Nikula et al , 2000;Ribeiro-Paes et al, 2009, 2011, 2012.…”
Section: )unclassified
See 2 more Smart Citations